Establishing the Reaction Pathways of the Catalytic Conversion of Erythrulose to Sulphides of Alpha‐Hydroxy Thioesters and Esters. Issue 8 (18th February 2022) - Calderon‐Ardila, Sergio; Matthijssen, Joost; Van Huffel, Bart; Péruch, Olivier; Morvan, Didier; Bellière‐Baca, Virginie; Dusselier, Michiel; Sels, Bert F.
Abstract: Sulphides of alpha‐hydroxy thioesters and esters (SAH(T)Es) are important fine chemicals and have great potential as platform molecules. SAH(T)Es are typically synthesized from fossil sources while little is known regarding their synthesis from carbohydrates. We report our findings about the one‐pot chemocatalytic conversion of erythrulose (ERU) to SAH(T)Es. Sn, Mo and W chlorides were the most selective catalysts towards the synthesis of S‐butyl‐4‐butylthio‐2‐hydroxybutanethioate (BBTHBT) in 1‐BuSH. The selectivity towards BBTHBT was impacted by the formation of different thioacetals (TAs). The addition of either KOH, H2 O or MeOH was effective to decrease TAs formation and increase selectivity towards BBTHBT (or its ester). A kinetic profile, in situ 13 C NMR measurements and experiments at different temperatures complement our studies to unravel the complicated reaction network involved in the conversion of ERU to SAH(T)Es. This insight provides a solid foundation for future improvements in the sustainable synthesis of SAH(T)Es. Abstract : We studied the Lewis acid catalyzed conversion of erythrulose to sulphides of alpha‐hydroxy thioesters and esters (SAH(T)Es). The addition of KOH, H2 O or MeOH to the reaction mixture increased the selectivity towards SAH(T)Es by decreasing the thioacetalization side‐reactions. Our findings allowed to propose a reaction pathway that unravels the reaction network with placement of the most important intermediates and products of the reaction cascade.